O viés da moda alinhado ao turismo: a influência das dicas de turismo publicadas em blogs de moda e beleza - Bosco, Giovana Miras (Universidade Federal de São Carlos, 2015)
The aim of this work is to analyze the behavior of 21st century female consumers through information about tourism on fashion and beauty blogs. To this end, a panorama of post-modernity, technology and consumption was presented. Next, the information published on these fashion and beauty blogs about travel was analyzed and compared with the opinions of travel agencies, readers and bloggers. In order to understand the influence that these blogs have on the 21st century consumer, and to point out the new trends, characteristics and opportunities for tourism companies.
The fashion bias aligned with tourism: the influence of tourism blogs published on fashion and beauty blogs
Keywords: Turismo; Consumo; Moda; Tourism; Consumption; Fashion; CIENCIAS SOCIAIS APLICADAS::TURISMO